A polymorphism in the TH2 locus control region is associated with changes in DNA methylation and gene expression. Issue 9 (14th July 2014) - Schieck, M.; Sharma, V.; Michel, S.; Toncheva, A. A.; Worth, L.; Potaczek, D. P.; Genuneit, J.; Kretschmer, A.; Depner, M.; Dalphin, J.‐C.; Riedler, J.; Frei, R.; et al.
Abstract Background Genomewide association and epigenetic studies found a region within the RAD50 gene on chromosome 5q31 to be associated with total serum IgE levels and asthma. In mice, this region harbors a locus control region for nearby TH2 cytokines, which is characterized by four Rad50 DNase I hypersensitive sites (RHS4–7). Among these, RHS7 seems to have the strongest impact on TH2 differentiation. We investigated whether within the human homolog of RHS7, functional polymorphisms exist, which could affect DNA methylation or gene expression in the 5q31 locus and might have an influence on asthma status or IgE regulation. Methods The human RHS7 region was fine mapped using 1000 genomes database information. In silico analysis and electrophoretic mobility shift assays were used to assess SNP function. Allele‐specific effects on DNA methylation were evaluated in cord blood (n = 73) and at age of 4.5 years (n = 61) by pyrosequencing. Allele‐specific effects on RAD50, IL4, and IL13 expression were analyzed in 100 subjects. Associations with asthma and IgE levels were investigated in the MAGICS/ISAAC II population (n = 1145). Results Polymorphism rs2240032 in the RHS7 region is suggestive of allele‐specific transcription factor binding, affects methylation of the IL13 promoter region and influences RAD50 and IL4 expression (lowest P = 0.0027). It is also associated with total serum IgE levels (P = 0.0227). Conclusion A functional relevant polymorphism in the TH2 locus control region, equivalent to RHS7 in mice, affects DNA methylation and gene expression within 5q31 and influences total serum IgE on the population level.